Metabolic progression to clinical phenotype in classic Fabry disease. Issue 1 (December 2017) - Spada, Marco; Kasper, David; Pagliardini, Veronica; Biamino, Elisa; Giachero, Silvana; Porta, Francesco
Abstract Background Fabry disease is an X-linked lysosomal storage disorder due to α-galactosidase A (α-Gal A) deficiency. Clinical onset of Fabry disease is preceded by significant storage of globotriaosylceramide (Gb3) and related glycosphingolipids, but the extent of the metabolic progression before symptoms is unknown. Using a newly recognized effector and marker of Fabry disease, globotriaosylsphingosine (LysoGb3), we aimed to provide a metabolic picture of classic Fabry disease from the neonatal period to childhood. Methods LysoGb3 was assessed at different times in two brothers with classic Fabry disease (genotype c. 370–2 A > G). The firstborn was diagnosed after clinical onset at 11 years of age, whereas the second-born was diagnosed in the neonatal period. LysoGb3 was measured in dried blood spots by high-sensitive electrospray ionization liquid chromatography tandem mass spectrometry. Results Blood LysoGb3 concentrations were consistent with patients' age and clinical picture, with lower levels in the asymptomatic neonate (19.1 ng/ml) and higher levels in the symptomatic child (94.3 ng/ml). In the second-born, LysoGb3 doubled during the first 5 months of life (37.4 ng/ml), reaching ~40% concentration observed in the symptomatic period. The neonatal LysoGb3 concentration in classic Fabry disease exceeded that observed in normal subjects by over 15 times. Conclusions A substantial increase of LysoGb3 was documented during the first months of life in classic Fabry disease, suggesting an early plateau during the pre-symptomatic period. Such a progressive metabolic trend during the pre-symptomatic period implies the potential definition of a metabolic threshold useful for a preventive therapeutic approach of classic Fabry disease. Additionally, the consistent increase of LysoGb3 in the neonatal period in classic Fabry disease suggests LysoGb3 as a useful marker for improving the specificity of newborn screening for Fabry disease.